Determinants of Stunting in Children Aged 6-59 Months in Glagah Sub-District, Indonesia - Moch Thoriq Assegaf Al-Ayubi; Fajar Ariyanti (Jurnal Berkala Epidemiologi, 2021)
Background: According to basic health research in Indonesia from 2018, the national prevalence of stunting among children under five is 30.80%. Half of the ten highest-priority villages for national stunting interventions in the Lamongan District are located in Glagah Sub-district. Purpose: This study aimed to identify the determinants of stunting in children aged 6 to 59 months in the Muslim population in the Glagah Sub-district, Lamongan District, 2019. Methods: The design of this study was an analytic observational case-control. The population was mothers with children aged 6 to 59 months in Glagah Sub-district. The samples comprised 44 cases and 88 controls. They were paired with matching variables, including gender and clean water sources. Cluster sampling techniques and probability proportional to the size sampling method were utilized to calculate the sample size for each cluster. Data collection was carried out using a modified research questionnaire. Research was carried out in June–July 2019. Bivariate analysis was performed with chi-square and independent t-tests at the significance level α= 0.05. Results: The factors found to be related to stunting were bodyweight at birth (p-value 0.01; eta2 0.09), protein intake (p-value 0.01; eta2 0.12), energy intake (p-value 0.01; eta2 0.19), maternal height (p-value 0.01; eta2 0,08), and parenting pattern (p-value 0.03; ORpermissive 3.33, ORmoderate 1.69). Conclusion: Determinants associated with stunting were bodyweight at birth, protein and energy intake, maternal height, and parenting pattern. Integrated Service Post officers can provide education and workshops on good parenting patterns to parents of toddlers.